Immunogenicity of high-dose trivalent inactivated influenza vaccine: a systematic review and meta-analysis. (4th March 2019) - Samson, Sandrine I.; Leventhal, Phillip S.; Salamand, Camille; Meng, Ya; Seet, Bruce T.; Landolfi, Victoria; Greenberg, David; Hollingsworth, Rosalind
ABSTRACT: Introduction : High-dose trivalent, inactivated, split-virus influenza vaccine (IIV3-HD) has been available in the US since 2009 for adults aged ≥ 65 years. To better understand how IIV3-HD provides improved protection against influenza, we systematically reviewed clinical studies comparing immune responses to IIV3-HD and standard-dose trivalent vaccine (IIV3-SD). Areas covered : The primary objective was to determine the relative hemagglutination inhibition (HAI) antibody response of IIV3-HD vs. IIV3-SD in adults aged ≥ 65 years. Based on seven randomized studies including more than 18, 500 adults aged ≥ 65 years, combined HAI geometric mean titer (GMT) ratios (95% confidence interval) approximately 1 month post-vaccination were 1.74 (1.65–1.83) for influenza A/H1N1, 1.84 (1.73–1.95) for influenza A/H3N2, and 1.47 (1.36–1.58) for influenza B. HAI GMT ratios in these studies were similar irrespective of sex, older age (≥ 75 years), frailty, and underlying conditions. Trends were similar for A/H3N2 neutralization and anti-neuraminidase antibody titers. In immunocompromised individuals, HAI GMT ratios were mostly > 1. Expert opinion : In agreement with its improved efficacy and effectiveness, IIV3-HD is consistently more immunogenic than IIV3-SD in adults aged ≥ 65 years. IIV3-HD also appears more immunogenic in immunocompromised individuals.